2013
DOI: 10.1111/irv.12181
|View full text |Cite
|
Sign up to set email alerts
|

International flight‐related transmission of pandemic influenza A(H1N1)pdm09: an historical cohort study of the first identified cases in the United Kingdom

Abstract: BackgroundTransporting over two billion passengers per year, global airline travel has the potential to spread emerging infectious diseases, both via transportation of infectious cases and through in-flight transmission. Current World Health Organization (WHO) guidance recommends contact tracing of passengers seated within two rows of a case of influenza during air travel.ObjectivesThe objectives of this study were to describe flight-related transmission of influenza A(H1N1)pdm09 during a commercial flight car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…Infection during flights has been found to have a significant probability. Even though aircraft are equipped with High-Efficiency Particulate Air (HEPA) filters, which reduce the risk of transmission through the air circulation system, several studies have demonstrated that infection rates can be as high as 4.3% in a 9-h flight, and that the risk does not depend on the relative seating of contagious passengers and passengers infected in-flight [29]. Mangili and Gendreau already discussed the need for additional work on in-flight transmissions [30], but insufficient data have been made available in the meanwhile to allow a more robust conclusion.…”
Section: Limitations To Predictive Capacitymentioning
confidence: 99%
“…Infection during flights has been found to have a significant probability. Even though aircraft are equipped with High-Efficiency Particulate Air (HEPA) filters, which reduce the risk of transmission through the air circulation system, several studies have demonstrated that infection rates can be as high as 4.3% in a 9-h flight, and that the risk does not depend on the relative seating of contagious passengers and passengers infected in-flight [29]. Mangili and Gendreau already discussed the need for additional work on in-flight transmissions [30], but insufficient data have been made available in the meanwhile to allow a more robust conclusion.…”
Section: Limitations To Predictive Capacitymentioning
confidence: 99%
“…In general, these techniques are not entirely effective in preventing the spread of viral infectious disease because passengers, either with a fever or presenting symptoms with respiratory virus infections such as influenza virus, often shed viruses before they have fever. A notable example of the failure of screening methods occurred in 2009 during the spread of influenza A(H1N1) pdm09 virus, where passengers on a flight from Cancun Mexico were screened but still managed to infect other passengers during flight [2].…”
Section: Introductionmentioning
confidence: 99%
“…With over three billion airline passengers annually, the risk of in-flight transmission of infectious disease is a vital global health concern [1, 2]. Over two dozen cases of in-flight transmission have been documented, including influenza [3][4][5][6][7], measles [8,9], meningococcal infections [10], norovirus [11], SARS [12,13], shigellosis [14], cholera [15], and multi-drug resistant tuberculosis [1,[16][17][18]. Studies of SARS [12,13] and pandemic influenza (H1N1p) [19] transmission on airplanes indicate that air travel can serve as a conduit for the rapid spread of newly emerging infections and pandemics.…”
Section: Introductionmentioning
confidence: 99%